Cicatricial Ectropion After Maxillofacial Surgery: Poster Presentation - Case Report - General practitioner - Lisa Berliani Tanaya; Sari Marina (Majalah Oftalmologi Indonesia, 2023)
Introduction : cicatricial ectropion is a malposition lower eyelid by shortening and/ or scarring of the anterior lamella of eyelid but it can occur in the upper eyelid. Ocular manifestations in cicatricial ectropion occurred epiphora, redness eyes, foreign body sensation, dry eyes due to direct exposure to the outside. In severe case may occur ulceration and loss of vision Case Illustration : A 33 year old male patient was being came to ophthalmologist department at Bali Mandara General Hospital with complaints that the right eye could not close completely, the felt dry eyes, foreign body sensation, and sometimes redness eyes after maxillofacial surgery one month ago before admitted to hospital. The physical examination the patient was normal. The ophthalmological examination visual acuity 6/6 for both eyes, intraocular pressure was normal for both eyes. The movement of the eyeballs was normal. The segment anterior examination was a scar on the lower right eyelid, inferior palpebral retraction, lagophthalmos 4 mm. The segment anterior examination of the left eye was normal. Discussion : The patient was treated to repair the cicatricial ectropion with surgery under general anesthesia with postauricular full thickness skin graft, antibiotic eye ointment, antibiotic oral, and lubricant eye drop. Conclusion : Cicatricial ectropion is a complication that occurs due to trauma or surgery. Reconstructive surgery to repair eyelid function, improve cosmetic appearance and minimize complications of further eye damage such as keratitis to blindness. Knowing the etiology along with the progression of the disease is necessary for early diagnosis and prompt treatment.